A Mediterranean diet improves HbA1c but not fasting blood glucose compared to alternative dietary strategies: a network meta‐analysis. Issue 3 (22nd June 2013) - Carter, P.; Achana, F.; Troughton, J.; Gray, L. J.; Khunti, K.; Davies, M. J.
Abstract Background Overweight or obese individuals with type 2 diabetes are encouraged to lose weight for optimal glucose management, yet many find this difficult. Determining whether alterations in dietary patterns irrespective of weight loss can aid glucose control has not been fully investigated. Methods We conducted a systematic review and meta‐analysis aiming to determine the effects of a Mediterranean diet compared to other dietary interventions on glycaemic control irrespective of weight loss. Electronic databases were searched for controlled trials that included a Mediterranean diet intervention. The interventions included all major components of the Mediterranean diet and were carried out in free‐living individuals at high risk or diagnosed with type 2 diabetes. Network meta‐analysis compared all interventions with one another at the same time as maintaining randomisation. Analyses were conducted within a Bayesian framework. Results Eight studies met the inclusion criteria, seven examined fasting blood glucose (n = 972), six examined fasting insulin (n = 1330) and three examined HbA1c (n = 487). None of the interventions were significantly better than the others in lowering glucose parameters. The Mediterranean diet reduced HbA1c significantly compared to usual care but not compared to the Palaeolithic diet. Conclusions The effect of alterations in dietary practice irrespective of weight loss on glycaemic control cannot be concluded from the present review. The need for further research in this area is apparent because no firm conclusions about relative effectiveness of interventions could be drawn as a result of the paucity of the evidence.